'… For the love of children and the joy of childhood': The reported values, beliefs and practices of male practitioners in England. (December 2016) - Jones, Charlotte Estella
Increased attention has been paid to qualifications and training of early childhood education and care staff in order to improve the quality of the service they provide. However, less attention has been paid to the demographics of the workforce itself. Men have consistently made up 2 per cent of the early childhood education and care workforce. Research on their experiences within the workforce is lacking and therefore their work with young children largely unreported. Drawing on data collected from an online questionnaire, this article will explore the reported values, beliefs and experiences of male practitioners working with children aged 0–5 years. Bourdieu's theories on habitus, capital and field were utilised as a means of interrogating data gathered to consider influences shaping life chances and practices of men working with young children. Participants shared extremely positive experiences of their current work; however, the findings reflected the need to reconsider the extent to which our cultural conceptions of gender roles and identities have changed in the sphere of early childhood education and care in the 21st century.